High-TSH Subclinical Hypothyroidism Is Associated With Postoperative Mortality in Acute Type A Aortic Dissection - Wang, Shi-Pan; Xue, Yuan; Li, Hai-Yang; Jiang, Wen-Jian; Zhang, Hong-Jia (Frontiers in Endocrinology, 2022)
Background Subclinical hypothyroidism can negatively affect the cardiovascular system and increase the risk of mortality, especially for individuals with thyroid-stimulating hormone (TSH) levels above 10 mU/L. We investigated the relationship between high-TSH subclinical hypothyroidism and postoperative mortality in acute type A aortic dissection (ATAAD) patients. Method We enrolled 146 patients with ATAAD who underwent aortic surgery in Beijing Anzhen Hospital from July 2016 to November 2018. Thyroid hormone levels were obtained before surgery, and participants were divided into a ≥10mU/L TSH level group and a <10mU/L level group. Cox proportional hazard regression and subgroup analysis were conducted to examine the association of preoperative high-TSH subclinical hypothyroidism with postoperative mortality. Result Participants with preoperative high-TSH (≥10mU/L) subclinical hypothyroidism tended to have longer hospitalization stays after surgery [16.0 (IQR 11.0-21.0) days vs 12.5 (IQR 8.0-16.0) days, P=0.001]. During the first 30 days after operation, 15 of 146 patients died (10.3%); during a median of 3.16 (IQR 1.76-4.56) years of follow-up, 24 patients died (16.4%). Cox proportional hazard regression showed that preoperative high-TSH subclinical hypothyroidism was independently associated with 30-day mortality (HR=6.2, 95% CI, 1.7-22.0, P=0.005) and postoperative mortality after adjusting for age, sex, BMI, hypertension, ejection fraction, diabetes and history of PCI (HR=3.4, 95% CI, 1.4-8.0, P=0.005). Conclusion This study showed that preoperative high-TSH subclinical hypothyroidism was an independent predictor of postoperative mortality in ATAAD patients who underwent aortic surgery.